Analisis problem-solving skills IPAS materi perubahan wujud benda pada peserta didik kelas IV sekolah dasar - Fauziah, Maryam Nurul; Matsuri, Matsuri; Saputri, Dwi Yuniasih (Universitas Sebelas Maret, 2025)
This study aims to analyze the problem-solving skills of fourth-grade elementary school students in understanding changes in the state of objects. The study was conducted at SDN Dukuhan Kerten using a quantitative survey method, involving 26 students. The instrument used was a descriptive test with three questions covering the concepts of melting and freezing, evaporating and condensing, and sublimating and crystallizing. The results of the analysis showed that students had difficulties, especially in planning and implementing solutions. In question number 1 (melting and freezing), the greatest difficulty lies in planning problem solving, with a percentage of conceptual understanding of 73%. In question number 2 (evaporating and condensing), the main difficulty is implementing the plan, although the percentage of indicator achievement is the highest (61.8%). In question number 3 (subliming and crystallizing), conceptual errors and implementing the plan are the biggest challenges, although problem evaluation shows the highest achievement (56.4%). Theoretical implications show the importance of teaching that combines conceptual understanding with high-level cognitive skills, while practical implications require educators to strengthen planning and implementing solutions in learning and integrate real-life situations and evaluation of problem-solving as an integral part of the learning process.